METHODS OF USING MULTISIM IN TEACHING ELECTRICAL ENGINEERING - Eshniyozov U. A. (Modern American Journals, 2025)
The article describes the organization of teaching electrical engineering using the modern digital innovative interactive program Multisim. Information about students' interest in research work is provided.
Keywords: Modern information technologies, pedagogy, innovative technologies, Multisim program.